ANALISIS PENGUNGKAPAN LINGKUNGAN TERHADAP KINERJA KEUANGAN DAN KINERJA SAHAM ( Studi pada Sektor Perusahaan Pertambangan ) - Nursasi, Enggar (DINAMIKA DOTCOM, 2017)
The purpose of this study was to identify and analyze environmental disclosure impact on the financial performance and stock performance. Sample companies in this study is a public mining company listed on the Indonesia Stock Exchange. Criteria sample is a mining company consistently listing on the Stock Exchange from 2009 to 2013 there were reports of the independent auditor on the companys financial statements, respectively. Data analysis was performed using a hypothesis test Partial Least Square (PLS). The sample was taken purposively sampled as many as 14 mining companies. Hypothesis testing results indicate that there is significant influence between environmental disclosure on financial performance and stock performance. This can be explained that disclosure of the acquisition environment is reflected by the ratings on PROPER will affect the companys operations in the profit. Means that the wider community has been attention to the role of companies on the environment. So that the companys concern for the environment will be welcomed by the public response to the business and the companys products. Which ultimately creates loyal customers that have an impact on sales and profits. Likewise for stock performance is affected by the environmental disclosure by the company. This means the shareholders of linking the companys activities in terms of disclosure of environmental performance in conducting transactions with companies in the investment process and investment. This can be explained that the submission of environmental disclosure and PROPER good acquisition by the company in the annual report, it will affect the confidence of investors. The content of the information will cause investors reacted to the sale or purchase of shares. Furthermore, the reaction will be reflected in changes in stock returns around the date of publication of the financial statements. Â Keywords: Environmental Disclosure, Financial Performance, Return on Assets and Equity Return.